Educational package, stress and anger management, book therapy, play therapy, children - Khajenezami , Elham; Razavi , Vida sadat; Andishmand , Vida; Soltani , Amanallah (Applied Family Therapy Journal (AFTJ), 2023)
Aim: The aim of this study was to design and validate a stress and anger management training package based on book therapy and play therapy in primary school children in Kerman province: Method: This research is multifaceted. Led to the choice of a qualitative-quantitative mixed research method). Among the mixed research methods, a sequential mixed exploratory research design will be used. In order to collect data, in addition to using library studies and theoretical foundations derived from content analysis, in-depth semi-structured interviews will be used for further understanding. Results: The results of this study show that play therapy, story therapy packages can be used by psychologists to treat stress and anger in children. The results also showed that the mean of aggression and stress after using play therapy and book therapy, decreased significantly. Conclusion: The findings of this study indicate that the use of these methods reduces children's stress and increases their acceptance in society.